METACOGNITIVE CHEMISTRY EDUCATION STUDENTS IN SOLVING CHEMICAL EQUILIBRIUM PROBLEMS - Issaura Sherly Pamela; Fuldiaratman; Minarni (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
Problem solving is a process used to solve problems. The problem solving process involves metacognitive activities for someone who can explore metacognitive thinking skills, especially in regulating and controlling cognitive activities. Learning in chemistry education leads students to explore metacognitive thinking skills through problem solving. One of the materials that is the problem is chemical equilibrium. Solving chemical equilibrium problems requires good metacognitive skills. This study aims to describe the metacognitive skills of chemistry education students in solving chemical equilibrium problems. This research is a descriptive qualitative research. The research data were descriptive texts of students' metacognitive skills in problem solving which were collected through problem solving tests and interviews. The test results obtained were analyzed qualitatively. Metacognitive skills data analysis techniques from the interview results using the analysis model of Miles and Huberman. The research subjects were 32 students of Education Chemistry Study Program, Education and Teacher Training Faculty, Jambi University. The results showed that 4 students did problem solving by just experimenting, so that the tests that were carried out were not quite right. The results of the interview stated that the students did not understand the problems in the questions. 14 students had difficulties and were confused about problem solving solutions but their understanding of the problems was quite good. The results of the interview stated that the students were aware of their weaknesses. 7 students were able to solve problems and check problem solving. The results of the interview stated that the students realized that there was a mistake in solving the problem given, but the students were hesitant to correct the error. 7 students demonstrated near-perfect overall problem solving skills and rechecking their work. The results of the interview stated that the students were aware of their abilities.